MORAXELLA CATARRHALIS BACTEREMIA ASSOCIATED WITH THIRD MOLAR SURGERY - N.CHITRA (International Journal of Pharma and Bio Sciences, 2014)
The bloodstream is sterile under normal conditions. Transient bacteremia occurs when bacteria enter the bloodstream. Bacterial species; general health care of the patient; and type of dental procedures are effective on the emergence of bacteremia complications. Moraxella catarrhalis is an exclusively human commensal of the upper respiratory tract and oral cavity. As Moraxella catarrhalis has been considered as a harmless commensal , very less is known about its pathogenic characteristics and virulence. However its role as a potential pathogen, has long been questioned. The aims of this study were to investigate the prevalence of transient bacteremia caused by Moraxella catarrhalis after third molar impactions. Also to find whether Moraxella catarrhalis bacteremia can occurs even after prophylactic administration of Amoxicillin